In memoriam. Richard Erskine Leakey (1944-2022). - (:unkn) unknown (My University, 2022)
Richard Leakey died at his home at Ngong, near Nairobi, in Kenya, on January 2, 2022. His career—which extended well beyond the confines of human origins research—has been comprehensively recorded in obituaries in national newspapers in the USA and elsewhere. Richard Leakey's contributions to paleoanthropology have been summarized,1 but his legacy includes the work of the many researchers who were influenced by his example to contribute in a variety of ways to human origins-related research. In this appreciation, a small sample of those individuals was invited to write and reminisce about the different ways Richard Leakey's interest and encouragement affected their lives and careers.
Keywords: African Research